"I saw a wrong and I wanted to stand up for what I thought was right:" A narrative study on becoming a breastfeeding activist - Jennifer Pemberton (Adult Education Research Conference, 2016)
Breastfeeding women experience marginalization in a number of ways, such as sexualization of the body and systemic influences that make it difficult for mothers to successfully breastfeed. This narrative study investigates how breastfeeding women come to recognize this marginalization and the emancipatory learning process through which they become breastfeeding activists.
Keywords: emancipatory learning; women' s learning; marginalization